ChemInform Abstract: A Practical Regioselective Synthesis of Alkylthio‐ or Arylthioindoles Without the Use of Smelly Compounds such as Thiols. Issue 33 (25th July 2013) - Hamashima, Toshihiko; Mori, Yoshiaki; Sawada, Kazunori; Kasahara, Yuko; Murayama, Daisuke; Kamei, Yuto; Okuno, Hiroaki; Yokoyama, Yuusaku; Suzuki, Hideharu
Abstract A series of 3‐alkylthio‐ and 3‐arylthioindoles is prepared by treatment of indoles with sulfoxides and TFAA followed by dealkylation of resulting sulfonium perchlorates in refluxing dipropylamine.